Randomized controlled trial of ultra-protective vs. protective ventilation strategy in veno-arterial extracorporeal membrane oxygenation patients with refractory cardiogenic shock: a study protocol for the ultra-ECMO trial - Li, Wei; Chen, Chen; Hu, Deliang; Sun, Feng; Zhang, Gang; Zhang, Zhongman; Dong, Yanbin; Lv, Jinru; Mei, Yong; Chen, Xufeng (Frontiers in Cardiovascular Medicine, 2023)
Background: Invasive mechanical ventilation(IMV) plays an important role as an adjunctive treatment means in patients treated by veno-arterial extracorporeal membrane oxygenation(VA-ECMO). By now, there is no consensus on mechanical ventilation parameter settings in patients with VA-ECMO, such as tidal volume, positive end-expiratory pressure(PEEP), as well as respiratory rate. Protective tidal volume is strongly recommended in critically ill patients, particularly patients suffering acute respiratory distress syndrome (ARDS). Moreover, ultra-protective tidal volume is also largely adopted in patients with veno-veno extracorporeal membrane oxygenatin(VV-ECMO). However, researches have not well demonstrated its promoting effect on IMV weaning in patients with VA-ECMO. Such patients may also benefit from an ultra-protective tidal volume strategy. The study aimed at investigating the effectiveness exhibited by ultra-protective tidal volume on the 28-day ventilator-free days(VFD) in VA-ECMO supported patients. Methods: The Ultra-ECMO trial is a randomized controlled, open-lable, single-centric prospective superiority trial. At the onset of ECMO initiation, we divide patients into the intervention group and the control group at 1:1 ratio in a random manner. The control group adopts protective ventilation setting (initial tidal volume: 6ml/kg predicted body weight, PBW) for ventilation, and the intervention group adopts ultra-protective ventilation setting(initial tidal volume: 4ml/kg PBW) for ventilation. The procedure is expected to last 72 hours ,after which the ventilator settings will be at intensivists’ discretion. The primary outcome is the ventilator-free day(VFD) number at day 28 after inclusion. The secondary outcomes include respiratory mechanics, analgesic/sedation dosage, lung ultrasound score(LUS), interleukin-6(IL-6), interleukin-8(IL-8) as well as monocyte chemotactic protein-1(MCP-1) level in broncho-alveolar lavage fluid(BALF), total length in day for ECMO weaning, length of stay(LOS) in ICU, total cost for hospitalization, in-hospital mortality. Discussion: VA-ECMO treated patients without ARDS possess abnormal lung function. CPE, thoracic compliance reduction, poor pulmonary blood perfusion are frequently present. It seems that protective tidal volume can lower adverse outcome incidence, even without ARDS. The purpose of this manuscript is to answer the question “Whether ultra-protective tidal volume can lead to superior outcomes compared to protective tidal volume in patients treated by VA-ECMO”. The Ultra-ECMO trial will provide an innovative mechanical ventilation strategy for VA-ECMO-supported patients.